Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

A = 2lw + 2lh + 2wh h=?

2 Answers

Relevance
  • Anonymous
    6 years ago
    Favorite Answer

    A = 2lw + 2lh + 2wh <-- subtract 2lw both sides of the equation..

    A - 2lw = 2lw - 2lw + 2lh + 2wh

    A - 2lw = 2lh + 2wh <-- factor out an 'h' out of the right hand side..

    A - 2lw = h (2l + 2w) <-- now divide both sides by (2l + 2w)

    (A - 2lw)/(2l + 2w) = h (2l + 2w)/(2l + 2w)

    (A - 2lw)/(2l + 2w) = h <--- answer...

  • Raj K
    Lv 7
    6 years ago

    A = 2lw + 2lh + 2wh h=

    → A−2lw=2h(l+w)

    →h=(A−2lw)/{2(l+w)}

Still have questions? Get your answers by asking now.